2007
DOI: 10.1103/physrevlett.98.097402
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Melting of a Stripe-Type Charge-Order and Metallic Domain Formation in a Layered BEDT-TTF-Based Organic Salt

Abstract: Photoinduced melting of charge-order (CO) in [bis(ethylenedithiolo)]-tetrathiafulvalene (BEDT-TTF) salts was investigated by femotosecond spectroscopy. Comparative studies on two polytypes exhibiting large [theta-(BEDT-TTF)2RbZn(SCN)_{4}] and small [alpha-(BEDT-TTF)2I3] molecular rearrangements through the CO transition were performed. Ultrafast melting of CO for both compounds demonstrates the major contribution of the electronic instability which is due to Coulomb interaction. The roles of the molecular rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 18 publications
(21 reference statements)
8
121
2
Order By: Relevance
“…This fast photoresponse was studied by Iwai et al, as a photoinduced insulator-to-metal phase transition. Using mid-infrared pump-probe spectroscopy, they observed the transient reflectivity change in the mid-infrared region [123,139]. The decay process depends on the intensity of the light pulse.…”
Section: α-(Bedt-ttf) 2 I 3 and Related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fast photoresponse was studied by Iwai et al, as a photoinduced insulator-to-metal phase transition. Using mid-infrared pump-probe spectroscopy, they observed the transient reflectivity change in the mid-infrared region [123,139]. The decay process depends on the intensity of the light pulse.…”
Section: α-(Bedt-ttf) 2 I 3 and Related Compoundsmentioning
confidence: 99%
“…Among the various known organic conductors [115][116][117][118], α-(BEDT-TTF) 2 I 3 (abbreviated as α-I 3 ) shows rich electronic properties such as charge ordering [119], superconductivity [120], zero-gap state (ZGS) [121,122], photo-induced phase transition [123], and nonlinear optical response [124].The crystal structure of α-I 3 consists of alternating layers of the anion and donor [125]. The donor layer has a herringbone arrangement of BEDT-TTF molecules.…”
Section: α-(Bedt-ttf) 2 I 3 and Related Compoundsmentioning
confidence: 99%
“…1a) in Mott insulators [4][5][6][7][8][9][10] , chargeordered (CO) systems [11][12][13][14] and charge/spin density wave materials 6,[15][16][17][18][19][20] . Recently, the excitation of coherent phonons has been established as a leading strategy for the melting/ constructing of electronic orders 8,9,[15][16][17][18][19][20] .…”
mentioning
confidence: 99%
“…13,14 In general, the system near the critical point shows a critical slowing down 22 and as mentioned earlier, in photoexcited - 14 In addition, Iwai et al have also reported a marked slowing down of the photoexcitation relaxation near superconducting transition temperature using an ultrafast pump-probe reflection spectroscopy. 23 Accordingly, the existence of the slow photoexcited relaxation dynamics might be a special property of the organic superconductors which arises from the complex electronic states. However, the mechanism of the nonbolometric photoresponse in the superconducting phase of the -(BETS) 2 4 has been studied with photoirradiation of the nanosecond laser pulse.…”
Section: Resultsmentioning
confidence: 99%
“…Light induced phase-transition phenomena of molecular conductors have been extensively studied and reported by several research groups: for example, a light-induced charge transfer in a donoracceptor stacked molecule, 5,6 a photoinduced phase transition from a charge-ordered insulating phase to a metallic phase in the organic conductor α-[bis(ethylenedithio)tetrathiafulvalene] 2 I 3 [α-(BEDT-TTF) 2 I 3 ] by using femtosecond pump probe spectroscopy and timeresolved photoresponse measurements of electrical conductivity. [7][8][9][10][11] Recently the insulator-metal transitions induced by electric field and photoirradiation in organic Mott insulator deuterated κ-(BEDTTTF) 2 Cu[N(CN) 2 ]Br has been reported by our group. 12 Moreover, photoexcitation dynamics of organic superconductors β-(BEDT-TTF) 2 I 3 together with its deuterated analog, and hydrogenated compound of κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br was also studied to elucidate the potential of the emergence of photoinduced superconductivity.…”
Section: Introductionmentioning
confidence: 99%